VALIDITY OF NATIONAL INDICATORS IN THE FIELD OF SUSTAINABLE DEVELOPMENT - Abduvaliyev , Abduqodir; Nayimov , Otabek (Scientific practical conference, 2025)
In the New Uzbekistan, the recognition by the international community of the profound structural socio-economic reforms being implemented to ensure the free and prosperous life of the country’s population indicates the high effectiveness of these reforms. In particular, along with other countries of the world, Uzbekistan also joined the United Nations (UN) General Assembly’s Sustainable Development Summit held in September 2015, adopting the Global Agenda for Sustainable Development Goals (SDGs) up to 2030 – a clear confirmation of this commitment.